CHARACTERISTICS OF THE TRANSLATION OF MODERN IT TERMINOLOGY FROM ENGLISH INTO UZBEK - Anarkulova Go’zal Abdurashid qizi (TADQIQOTLAR, 2025)
Abstract: ICT terms are a relatively new field for the Uzbek language, which has entered the Uzbek lexicon through Russian and directly through English. Therefore, most ICT terms have features specific to English lexicon. It has been decades since the first computers were created, and the last generation of computers has been aroundfor a long time, during which time computer language has gone beyond the scope of professional use and into the everyday speech of language owners.